EFL STUDENTS' PERCEPTIONS OF AI SPEECH RECOGNITION IN PRONUNCIATION PRACTICE: THE CASE OF GOOGLE READ ALONG - Sari, Fitriana Kartika; Kurniawan, Prasetyo Yuli (English Review: Journal of English Education, 2025)
The study aimed to exploring students’ perception of implementing AI Speech Recognition to facilitate students’ pronunciation in EFL Students context. Quantitative and qualitative data were gained by applying a questionnaire and interviews. The study conducted at Non-English and English Study Program from four different Universities: Universitas Muhadi Setiabudi, Universitas Pancasakti Tegal, Universitas Pekalongan, and Universitas Jenderal Soedirman. Respondents in this study were 45 students from the English study program who joining the Pronunciation course and 75 non-English students who joining the English course. The result showed that students have positive perceptions of the use AI Speech Recognition in Google Read Along Application to facilitate English pronunciation learning. At the same time, students also stated that application's functionality may need to be supplemented with other learning tools for more comprehensive pronunciation training and the Google Read application would be more optimal if there was collaboration with the lecturer. In conclusion, the Google Read Along application is an effective tool for enhancing students' pronunciation skills and providing valuable feedback.